(untitled) (L’architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2017)
More than half a century after they were built, a selection of highly successful public spaces in Latin America may help us understand a correct approach to the design of new public spaces today; the conceptual structures that led their designers to imagine these spaces for the city; the roles of landscaping and social relations that to some degree conditioned their design.